2013
DOI: 10.1007/s00125-013-2935-8
|View full text |Cite
|
Sign up to set email alerts
|

Double deficiency in IL-17 and IFN-γ signalling significantly suppresses the development of diabetes in the NOD mouse

Abstract: Aims/hypothesis T helper type (Th) 17 cells have been shown to play important roles in mouse models of several autoimmune diseases that have been classified as Th1 diseases. In the NOD mouse, the relevance of Th1 and Th17 is controversial, because single-cytokinedeficient NOD mice develop diabetes similarly to wildtype NOD mice. Methods We studied the impact of IL-17/IFN-γ receptor double deficiency in NOD mice on the development of insulitis/diabetes compared with IL-17 single-deficient mice and wild-type mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 43 publications
(61 reference statements)
2
60
0
2
Order By: Relevance
“…Today, this leads to the notion that both IL-12 and IL-23 as well as T H 1 and T H 17 cells are synergistically implicated in experimental autoimmune diabetes [61]. This matches with the finding that genetic ablation of the both effector cytokines IFN-γ and IL-17 acts synergistically to prevent diabetes [71].…”
Section: Page 17 Of 33supporting
confidence: 58%
“…Today, this leads to the notion that both IL-12 and IL-23 as well as T H 1 and T H 17 cells are synergistically implicated in experimental autoimmune diabetes [61]. This matches with the finding that genetic ablation of the both effector cytokines IFN-γ and IL-17 acts synergistically to prevent diabetes [71].…”
Section: Page 17 Of 33supporting
confidence: 58%
“…It has been reported that IL-17 knock-out (KO) NOD mice showed a delayed onset of diabetes and milder insulitis, while the long-term follow-up of these animals revealed an incidence of the disease overlapping that of wild type animals [41]. These findings may suggest that IL-17 and therefore Th17 cells may be crucial for triggering autoimmunity in the early stages of the disease.…”
Section: Discussionmentioning
confidence: 94%
“…We thus propose a derepression model whereby ChMBC7 promotes Th17 cell differentiation by inhibiting the suppressive effect of IL-2. A number of studies have proposed that Th17 cells played a disease-promoting role in T1D (47,48), mainly through their signature cytokine IL-17 (49)(50)(51)(52)(53)(54) or, alternatively, through TNF-α produced by Th17 cells (55). However, this opinion was contradicted by other studies suggesting that Th17 cells may possess a disease-suppressive role in T1D (56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%